Resistance of Xanthomonas euvesicatoria strains from Brazilian pepper to copper and zinc sulfates - Areas, Maysa S. [UNESP]; Goncalves, Ricardo M.; Soman, Jose M. [UNESP]; Souza Filho, Ronaldo C. [UNESP]; Gioria, Ricardo; Da Silva Junior, Tadeu A. F.; Maringoni, Antonio C. [UNESP] (Acad Brasileira De Ciencias, 2018)
Bacterial spot, caused by Xanthomonas spp., is one of the major bacterial diseases in pepper (Capsicum annuum L.). The infection results in reduced crop yield, particularly during periods of high rainfall and temperature, due to the low efficiency of chemical control with copper bactericides. This study evaluated the copper and zinc sulfate sensitivity of 59 pathogenic strains of Xanthomonas euvesicatoria isolated from pepper plants produced in various regions throughout Brazil. Both the respective sulfates and a mixture thereof was evaluated at 50, 100, 200 and 400 mu g.mL(-1). All the evaluated strains were found to be resistant to zinc sulfate (100 mu g.mL(-1)) and 86.4% were resistant to copper sulfate (200 mu g.mL(-1)). The mixture of copper (200 mu g.mL(-1)) and zinc (200 mu g.mL(-1)) sulfates inhibited the growth of all strains of X. euvesicatoria. To our knowledge this is the first study to report the resistance of X. euvesicatoria strains from pepper plants to copper and zinc sulfates in Brazil.
Keywords: Bacterial spot; Capsicum annuum; chemical sensitivity; control